Simulation of liquid hydrocarbon production via n-tetradecane reforming: A renewable energy approach - Abolfazl Farajzadeh; Fatemeh Bahadori (PLoS ONE, 2026)
Considering the current worldwide search for renewable energy, n-tetradecane has attracted attention as a candidate for a hydrogen energy carrier and more sighted for light hydrocarbon within the gasoline range of C 5 -C 12 . This study investigates the production of liquid hydrocarbons by n-tetradecane in two stages process: syngas production through reforming of n-tetradecane and Fischer-Tropsch synthesis. The temperature, oxygen-to-carbon (O 2 /C) ratio, reactor length-to-diameter (L/D) ratio, and steam-to-carbon (S/C) ratio are examined in this study as the parameters that influence the reforming of n-tetradecane and superior result of 800ºC, 0.356 O 2 /C, 6 L/D and 2.3 S/C were established to give high conversion and efficient production of syngas. While the yield of the C 5 + hydrocarbon in the Fischer-Tropsch (FT) reactor increased with rising temperature up to 350°C, but the permissible temperature for process is 290°C, based on these, the temperature was set to optimize productivity and longevity of the catalyst. When using n-tetradecane as feed stock, high C 5 + production was resulted because of its suited H 2 /CO ratio of 2.3. The techno-economic assessment highlights the process’s viability at moderate scales, with economic performance strongly influenced by product price and energy integration.